Alternating-magnetic-field induced enhancement of diffusivity in Ni-Cr alloys. Issue 1 (December 2017) - Li, Chuanjun; He, Shengya; Engelhardt, Hannes; Zhan, Tongjun; Xuan, Weidong; Li, Xi; Zhong, Yunbo; Ren, Zhongming; Rettenmayr, Markus
Abstract For applying an alternating magnetic field (AMF) in materials processing it is of high significance to understand the physical mechanisms behind the change in diffusivity in the AMF. In this work, the effect of the AMF on interdiffusion in a Ni-Cr alloy was investigated with a diffusion couple. The interdiffusion coefficient was found to increase with increasing AMF intensity. The faster diffusivity is a consequence of the enhancement of the dislocation density in the diffusion couples that was confirmed by the broadening of X-ray diffraction peaks. The higher dislocation density is attributed to the magnetoplastic effect (MPE). Theoretical considerations on the relation of MPE, dislocation density and diffusivity are in agreement with the experimental results.